Fritz Redlich and the entrepreneur as God and demon - RAFAEL GALVÃO DE ALMEIDA (Brazilian Journal of Political Economy, 2023)
ABSTRACT This work recovers the contribution of Fritz Redlich (1892-1978) to the economic thought. Redlich wrote important works in the disciplines of economic history, entrepreneurship and business history. Amongst Redlich’s main ideas on the entrepreneur there is his distinction among different types of entrepreneurs. Redlich was also one of the first authors to analyze the structural problems of entrepreneurial action, proposing the idea of “demonic entrepreneur”, in which the accumulation of power caused by the entrepreneurial activity destroys the innovative spirit of the system, turning the entrepreneur into an enemy of society.